HDL-cholesterol elevation associated with fingolimod and dimethyl fumarate therapies in multiple sclerosis. Issue 4 (October 2019) - Blumenfeld Kan, S; Staun-Ram, E; Golan, D; Miller, A
Background: Patients with Multiple Sclerosis (PwMS) display altered lipoproteins levels and function, which seem to affect disease risk and progress. Whether disease-modifying therapies affect the lipoprotein profile in PwMS has scarcely been studied. Objective: The study aims to assess whether fingolimod and dimethyl fumarate (DMF) affect lipoproteins in PwMS. Methods: We compared retrospectively the blood lipoprotein levels of 29 fingolimod-treated and 41 DMF-treated patients before and after 3 and 12 months of therapy. Patients treated with cholesterol-reducing medications were not included. Data on weight change and disease activity during 1-year follow-up were obtained. Results: HDL level, HDL/LDL ratio and HDL/total cholesterol ratio were increased in both treatment groups after 3 months' therapy and sustained, with no change in LDL or triglycerides. While at baseline only 26% of patients met the recommended minimum of HDL 60 mg/dl, after 3 months' therapy, 43% of fingolimod-treated and 47% of DMF-treated patients reached the recommended level. The majority of patients had no weight reduction. Conclusions: Fingolimod and DMF therapies are associated with a specific increase in HDL in PwMS. Further studies are required to validate these findings and their potential implication as biomarker of reduced inflammatory state and/or reduced risk of neurodegeneration or cardiovascular comorbidity.